Implementation Of Digital Libraries In Digital Literacy Learning For Elementary School Students - Permatasari, Gina; Heryani, Rina; Sopandi, Wahyu; Komara, Intan Budi (International Conference on Elementary Education, 2025)
The development of digital literacy in primary schools has not progressed in line with the increasing availability of digital devices. This study analyzes the implementation of digital libraries in supporting digital literacy learning in a public primary school in Purwakarta Regency. Using a descriptive qualitative method, the study involved 25 participants consisting of one principal (4%), four teachers (16%), and 20 students from grades four and five (80%). Data were obtained through observation, semi structured interviews, and documentation, then analyzed using Miles and Huberman’s model of data reduction, data display, and conclusion drawing. The findings show that digital libraries expand students’access to information and enhance independence in searching for digital content, where 70% of students demonstrate high information-seeking autonomy. Teachers’ utilization of digital libraries is categorized as moderate (50%), while access to digital devices remains uneven, with only 35% of students in the high-access category. The use of digital libraries also strengthens students’ critical and reflective skills, although implementation is constrained by limited facilities, low teacher proficiency in managing digital shelves, and restrictive school policies particularly the ban on mobile phone use. Overall, digital librariesfunction as collaborative learning spaces that support the development of 21st-century competencies when supported by adequate infrastructure and flexible school regulations.